The Influence of Calcination Temperatures in TiO2 Impregnated Ouw’s Natural Clay on Its Degradation Activity of Methylene Blue Dye - Moylani Teddy; Catherina M. Bijang; Muh. Nurdin; Berly Kapelle (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2018)
The influence of calcination temperatures in TiO2 impregnated Ouw’s natural clay on its degradation activity of methylene blue dye has been done. Calcination process was conducted at various temperatures of 200, 300, and 400 oC. The characterization of TiO2 impregnated clay’s structure was examined by IR analysis. The result showed that Ouw’s natural clay has characterized vibrations of montmorillonite and thermal effect didn’t affect the structure of TiO2 impregnated clay. The highest result of methylene blue’s degradation occurred in the addition of TiO2 impregnated clay calcinated at 200 oC (98.69%). This result was found that calcination temperatures of impregnation process were significantly affect the degradation activity of TiO2 impregnated clays.